Turismo rural, sustentabilidade e o serviço público de extensão rural no estado de São Paulo - Pinho, Alexandre Mendes de (2014)
The contemporary extension comes across a rural area into new ruralities, including the inclusion of tourism, which can make allowance for the reorientation of its technical extension to new practices. The All-purpose Technical Assistance Coordination (from Portuguese, Coordenadoria de Assistência Técnica Integral CATI), an entity in which the act constituting the extension agents of this study, is the organ of the State Department of Agriculture and Food Supply responsible for actions of public extension with rural producers in the State of São Paulo. The absence of an institutional project focused on the rural tourism constituted motivation to gather aspects of care of the extension of CATI demand producers in this area as well as it realizes that there is a concern with a tour that is developed in a more sustainable way. In this sense, the goal of this dissertation was to survey elements on the perception of extension agents to justify the construction of an institutional program covering training activities and planning that will encourage them to expand their awareness and critical review of rural tourism phenomenon as a development vector. The research constituted of a recess, within the set of 645 municipalities of São Paulo, which considered those with rural tourism as prominent activity from two different criteria, resulting in a sample of 87 municipalities. To collect the data we used a questionnaire that sought, in the opinion of extension working with producers in the sampled counties, its profile and it characterizes its performance under rural tourism as well as to know their perception of the importance of the work of this extension segment and on sustainability elements related to tourism. From the collected data it was noted that, in general, the technical team acknowledges the role of the extension service in the context of rural tourism, as well as under the point of view of the development of economic activity, as the role of articulation and mediation that can be assumed by extension. However, this research pointed to some limitations that need to be overcome, namely: motivational issues, partly caused by the lack of incentives from the institution to standardize and to enhance the standard of care demands of tourism; the lack of specific technical knowledge on tourism; the need to increase their knowledge beyond environmental approach in the context of sustainable tourism development, with the expectation aid in understanding the strengths inherent to the phenomenon of tourism conflicts. Accordingly, an investment in differentiated capabilities would be essential in building a CATI statewide program, guided to the qualifying holding its extension agents in the context of rural tourism process.